Creating Superhydrophobic Polymer Surfaces with Superstrong Resistance to Harsh Cleaning and Mechanical Abrasion Fabricated by Scalable One‐Step Thermal‐Imprinting. Issue 16 (1st July 2019) - Zhan, Zhibing; Li, Zihao; Li, Xiaoyun; Garcell, Erik; Singh, Subhash; ElKabbash, Mohamed; Guo, Chunlei
Abstract: In this work, a scalable thermal imprinting method that allows to directly fabricate superhydrophobic polymer surfaces with superstrong resistance to harsh cleaning and mechanical abrasion is reported. A titanium (Ti) mold is produced by femtosecond laser processing to possess a hierarchical micro‐ and nanoscale pattern. Through thermal imprinting, this hierarchical pattern onto poly(propylene) sheets is able to be accurately reproduced, rending the polymer surface superhydrophobic. The imprinting method employed uses an aqueous ethanol solution of stearic acid to assist demolding, and periodically uses xylene to limit mold contamination and restore the mold to excellent condition for further imprinting. These strategies allow to repeatedly use the mold over 50 times without degradation. A range of durability tests are further performed, and showed that the produced suprehydrophobility on the poly(propylene) sheets exhibit excellent durability, withstanding brush washing, ultrasound cleaning, and sandpaper abrasion. The reported method can also be used to fabricate superhydrophobic surfaces of various thermoplastics that are broadly utilized in daily life. Abstract : Thermal imprinting approach to directly convert normal polymer surfaces to superhydrophobic surfaces (SHSs) is presented. The Ti mold produced by femtosecond laser processing can be used repeatedly without degradation. This scalable method can fabricate SHSs of various thermoplastics that are broadly utilized in daily life, which show superstrong resistance to harsh cleaning and mechanical abrasion.